Quality evaluations of heat shocked Philippine oysters (Crassostrea iredalei) - Perez, Vichiel Paula Villanueva (2006)
This study was done to establish Filipino consumer awareness on the safety concerns of raw oyster consumption and determine the effects of heat shucking on the quality of oyster meat. A face-to-face interview was done in public wet markets in Malabon, Navotas, Roxas, City, Capiz, and Kawit, Cavite, and Nepa-Q Mart and Farmers markets in Cubao, Quezon City. Survey results showed that almost 50% of the test consumers were aware of the safety risks of raw oyster consumption. The survey also proved the marketability of heat shucked oysters. Microbial quality assessment was done including Total Plate, Total Coliform, Generic Escherichia coli, and Total Vibrio spp. Counts. Heat shucking treatments were observed to significantly reduce the microbial population of oysters as the time and temperature exposure was increased particularly to those treated at 75 and 85°C. The TPC, TCC, GEC, and TVC range from 3.07 to 4.39, 2.65 top 3.77, <1.00 to 3.00, and 2.51 to 3.52 log10 CFU.g^-1, respectively. Microbial counts fell within acceptable limits and thus proved that heat shucking treatments provide oysters safe for human consumption. Sensory evaluation showed that heat shucked oyster meats at 65°C for 10 s as the most acceptable.